¿Por qué nació la juntura «Tradición Clásica»? Razones historiográficas para un concepto moderno - García Jurado, Francisco (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
The term «Classical Tradition» is a join of historiographical nature. It was thought mainly to signify a kind of relationship («a in b») between the Ancient and the Modern literatures, as far as the first ones were understood as an object of study different from the second ones. At the beginning, the terms of «tradition» and «traditional studies» were referred, by default, to the educated field of the Greek-Latin heritage. However, in a certain moment it was necessary to fix the adjective «classical», because of the progress of the studies on the new both folk and modern traditions. The old adjective «classical», a metaphor taken from the social field to point out the best authors in an idealistic and timeless literary republic, added a historical dimension to its aesthetic meaning: the classical literatures and languages, as a category referred to the Greek and Roman Antiquity. Likewise, the meaning of this adjective was restricted in opposition to «modern», «Christian» and «folk».